Roommating - Schorr, Meredith (Forever, 2025)
"Sabrina is too busy with grad school and her job as a library page to think about dating. Until Marcia, her elderly roommate, invites her estranged grandson Adam to move into their two-bedroom apartment in Manhattan temporarily to "find himself." Sabrina doesn't mind sharing the small space with Adam if it helps Marcia repair her relationship with her grandson. But she's not expecting to fall for him herself. Adam is not only gorgeous, he's kind, funny, shares her love of reading, and clearly adores Marcia. After one too many accidental midnight rendezvous in the bathroom (him shirtless), the tension between them is hotter than ever. But they're not the only ones feeling the heat. After Marcia has a health scare, her doctors advise that one of her younger roommates must go. In a comical and sexy battle to prove who deserves to stay, the two pull out all the stops. All's fair in love and real estate, but in the end victory is not so sweet when winning the apartment could mean losing each other"--